A Bibliometric Analysis of Public Transportation Management-Based Sustainable Development - Vera Sulistyana Devi Cristyani; Kismartini Kismartini (Spirit Publik: Jurnal Administrasi Publik, 2025)
Sustainable transport is one way to address the challenges associated with urbanization and support environmentally friendly, inclusive, and innovative city development. Trend analysis, evolution of themes and research opportunities in the field of public transport management with sustainable development perspective: A bibliometric study the research data was collected in the Scopus database by requesting publications using keywords, "transportation management," "sustainable development," "urban transportation," and "public transportation systems," which included 153 publications from 2000 to 2025 (as of May 24, 2025). Collaborations between countries, authors, and research clusters were visualized using VOSviewer software. Results indicate that publications on sustainable public transportation management are scarce, with a notable lack of international collaboration, and are mainly dominated by China, India, and Australia. Five major clusters were identified, namely sustainable development in conjunction with urban transport, traffic congestion and mode of transport, urban transport and public transit systems, urban planning and transportation plans, as well as sustainable transport utilizing renewable energy sources. Such a changing focus points to a growing body of work addressing the enabling of governance and policy arrangements of the clean energy transition. The complexity of management constructs remains entangled with the integration of energy policy and sustainability into transport management. While previous bibliometric studies primarily focused on the technical and service aspects of the literature, this study shifts the emphasis to the management and policy of clean energy. This emphasizes the need to streamline and integrate the low-carbon public transport systems. In this context, these findings provide a starting point for advocating collaborative studies across borders and the use of collaborative transport systems for evidence-based advocacy and policy development.